Variation in the nutrient content of different genotypes and varieties of millets, studied globally: a systematic review - Anitha, Seetha; Rajendran, Ananthan; Botha, Rosemary; Baruah, Chandrama; Mer, Pooja; Sebastian, Julia; Upadhyay, Shweta; Kane-Potaka, Joanna (Frontiers Media, 2024)
This study was conducted to understand the variation in the nutrient contents of different types of millets by collecting data from published scientific journals and collating it by variety. The data is analyzed as a whole and as a subset, where it is clearly categorized into a released variety or genotype/accession. Calcium level was consistently high in finger millet and teff regardless of varieties at 331.29 ± 10 mg/100 g and 183.41 ± 29 mg/100 g, respectively. Iron content was highest for finger millet at 12.21 ± 13.69 mg/100 g followed by teff at 11.09 ± 8.35 mg/100 g. Pearl millet contained the highest zinc content of 8.73 ± 11.55 mg/100 g. Protein content was highest in job’s tears at 12.66 g/100 g followed by proso millet at 12.42 ± 1.99 g/100 g and barnyard millet with 12.05 ± 1.77 g/100 g. Some millets showed consistently low or consistently high levels of specific nutrients, while others had such wide variation that they could not be characterized as high or low for that particular nutrient. There is a huge variation in the nutrient content of each type of millet regardless of the released variety or genotype. In the interest of improving dietary nutrients, there is a need to have nutrition programs and product development based on selected high nutrient varieties of the millet, which requires attention from researchers and government and changes in research, policy, and awareness among the public and private sectors.